Ecosystem Development Framework for Enterprise Data Science & Research Projects - Sukhdeve, Shitalkumar Rajendra (Digital Repository of Theses, 2023)
This research examines the development of an enterprise ecosystem for data science and research projects to unleash the full potential of data and foster innovation. The study proposes a comprehensive framework encompassing objective setting, firm performance evaluation, capability development, and strategic alignment. Industry experts and data science leaders from telecom, e-commerce, and financial sectors form the sample for interviews, which serve as the primary data collection method. Grounded theory is utilized for data analysis and theory development. The findings underscore the significance of objective setting, performance evaluation, capability development, and strategic alignment in optimizing processes and achieving superior outcomes. Organizations can cultivate innovation and gain a competitive edge by adopting this framework. The research contributes to effective data-driven decision-making and offers valuable insights for businesses operating in today's dynamic landscape.